1976
DOI: 10.3168/jds.s0022-0302(76)84408-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Dietary Zinc upon Zinc Metabolism and Intracellular Distribution in Cows and Calves

Abstract: Changes in the metabolism of zinc were investigated in mature nonlactating Holstein cows and 4-mo old calves fed high but nontoxic amounts of dietary zinc. Increasing dietary zinc of calves from 42 to 642 ppm elevated the zinc content of liver and pancreas 600% and 1400%, respectively. The elevated zinc in liver and pancreas involved a substantial increase in all intracellular fractions, with by far the largest amount associated with a 10,000 molecular-weight protein in the soluble cell fraction. This zinc-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…This was confirmed in a more extensive subsequent study, but the zinc which had accumulated with MT was found to be extremely labile ( 10) . Much of the zinc in liver and pancreas of calves fed 600 ppm zinc in the diet was associated with a low molecular weight protein ( MW), presumably MT 11 ), suggesting that young bovine ~pedes respond similarly to rats as far as zmc accumulation in tissue proteins is concerned. Other studies have been conducted on the .1ppearance of a zinc-binding protein in pancreas of rats ( 12).…”
mentioning
confidence: 99%
“…This was confirmed in a more extensive subsequent study, but the zinc which had accumulated with MT was found to be extremely labile ( 10) . Much of the zinc in liver and pancreas of calves fed 600 ppm zinc in the diet was associated with a low molecular weight protein ( MW), presumably MT 11 ), suggesting that young bovine ~pedes respond similarly to rats as far as zmc accumulation in tissue proteins is concerned. Other studies have been conducted on the .1ppearance of a zinc-binding protein in pancreas of rats ( 12).…”
mentioning
confidence: 99%
“…It has been reported that feeding a high Zn diet results in a great increase in the Zn content in a few tissues including the liver, pancreas, and kidney in calves , but not in cows1, [11][12][13][14]. Zn concentration in the liver of 2 newborn calves born from cows fed a low Zn diet in this study was higher than for cows, but not in the other tissues.…”
Section: Zn Analysis Of Samplesmentioning
confidence: 49%
“…KINKAID et al . 14) have reported that failure of tissue Zn to increase sharply in cows fed high dietary Zn may be due to the inability of cow tissues to retain excess Zn and, hence, a greater turnover rate. However, Mn7), Cu15), Se17), and cadmium (Cd)18) concentrations in the tissues of cows fed high levels of those elements were higher than those for untreated cows.…”
Section: Zn Analysis Of Samplesmentioning
confidence: 99%
“…However, as J concentrations in plasma and non thyroid tissues started to increase at 50 ppm J, the upper limit of 10 ppm would be preferable. In mature cows, homeostatic control mechanisms that regulate zinc (Zn) content in tissues are much more effective than in calves; therefore, mature cows probably are able to tolerate higher concentrations of dietary Zn (Kincaid et al, 1976). Davies et al (1977) reported suckling lambs were more susceptible to Zn toxicosis than mature animals.…”
Section: A Physiological State Age and Level Of Productionmentioning
confidence: 99%
“…Pregnant ewes also appear to be more susceptible to Zn toxicosis than non pregnant animals (Campbell and Mills, 1979). In all species, young growing animals appear to be more susceptible to Pb toxicosis than older animals, and ruminants more so than nonruminants (Neathery and Miller, 1976;Howell, 1996). Swine and poultry are more tolerant than ruminants to F toxicosis and tolerance seems to increase with age (NRC, 1980).…”
Section: A Physiological State Age and Level Of Productionmentioning
confidence: 99%